The impact of digital technology on the development of the nancial market - Fernandez, C. E.; Kalina, I. I. (НТУ ДП, 2023)
The impact of digital technology on the nancial market has been signi cant and far- reaching. In recent years, we have seen a rapid adoption of digital technologies such as blockchain, arti cial intelligence, and big data analytics, which have transformed the way nancial services are delivered and consumed. Digital technologies are transforming the nancial sector and improving ef ciency and the quality of life for people. They allow for time-saving and improved labor productivity by intensifying processes and saving time at all stages of transactions, resulting in more transactions per unit of time.
Keywords: digital; digital technology